Three-needle of regulating the mind combined with umbilical needle intervention for cervical vertigo with deficiency of qi and blood—A study protocol for a randomized controlled trial - Hou, Zhuanzhuan; Tian, Jun; Jin, Yuewei; Yu, Huida; Wu, Weigang; Wei, Miaomiao; Xu, Shibing (Frontiers in Neurology, 2025)
ObjectiveWith a higher incidence rate among the younger population, cervical vertigo (CV) can impose a significant burden on patients with CV. It is believed that a deficiency of qi and blood is the primary pathogenesis in Traditional Chinese medicine (TCM). Acupuncture is a vital strategy for CV, but the efficacy of current acupuncture therapies remains unsatisfactory. Thus, this randomized controlled study will assess the safety and effectiveness of three-needle of regulating the mind combined with umbilical needle (TNRM-UN) therapy for CV with qi and blood deficiency.MethodsThis was a single-center, assessor-, and analyst-blinded, prospective randomized controlled trial that involved treatment for 6 weeks and follow-up for 24 weeks. Ninety-nine patients with CV deficiency of qi and blood are randomly allocated to three groups in a 1:1:1 ratio. The patients in the observation group will receive three-needle of regulating the mind combined with umbilical needle (TNRM-UN) therapy. In contrast, the patients in the control-1 group will receive three-needle of regulating the mind combined with traditional acupuncture (TNRM-TA), and the patients in the control-2 group will receive only umbilical needle (UN) therapy. Primary outcomes include Cervical Vertigo Symptom and Functional Assessment Scale (CVS-FAS) score and qi and Blood Deficiency Symptoms Assessment Scale (QBD-SAS) score. The secondary outcomes are hemodynamic changes in the bilateral vertebral arteries, including diameter value (DV), peak systolic velocity (PSV), end-diastolic velocity (EDV), pulsatility index (PI), and resistance index (RI). All outcome measurements will be evaluated before and after 6 weeks of treatment. Primary outcomes will be evaluated at 12 and 24 weeks of follow-up. Adverse events (AEs) were evaluated during treatment and follow-up periods.ResultsThis study aimed to determine whether TNRM-UN is more effective than current acupuncture therapies by providing compelling evidence and deciding whether TNRM-UN can be used as a promising therapy for CV with a deficiency of qi and blood.Clinical trial registrationhttps://www.chictr.org.cn/, identifier: ChiCTR2400080759.